Identificación de peligros y riesgos en las estaciones de servicio de combustibles líquidos en la ciudad de Iquitos 2021 - Gonzales Tafur, Jose Gilberto (2024)
This thesis focused on the hypothesis of identifying hazards and evaluating risks to optimize the commercialization of liquid fuels in Iquitos service stations. The information was collected through field visits, observing the conditions of the facilities and the way in which the personnel carry out their activities in the maneuvering yard. The research was observational, non- experimental, transversal and simple descriptive. The NTP 330 accident risk standard was used, identifying three main activities: reception, storage and sale. The application of the IPER matrix made it possible to specify that the greatest probability of risks is found in the dispatch of fuels. The most important risks are fire, explosion and environmental contamination. The unsafe behavior of the personnel can be a determining factor of possible risks; likewise, it contributes to unfortunate scenarios. Service stations are open to the consuming public 24 hours a day, and by the very fact of storing fuel in underground tanks, they represent imminent dangers.